1973
DOI: 10.1073/pnas.70.2.310
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Proteolytic System by a Membrane Lipoprotein: Mechanism of Action of Tissue Factor

Abstract: One pathway of blood coagulation, the extrinsic system, is initiated by a specific interaction between tissue factor, which is a membrane lipoprotein, and factor VII, one of the plasma coagulation factors. Factor VII was prepared from bovine plasma by adsorption onto and elution from BaSO4. The eluate was chromatographed on DEAE-Sephadex and purified by preparative disc-gel electrophoresis. Factor VII complexed with purified bovine-brain tissue factor and, when eluted from the complex, factor VII had a greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…While the complete complex appears to be necessary for coagulant activity (12,17), the factor X converting site appears to reside in the factor VII molecule (18,19). In the bovine system, diisopropylphosphorofluoridate (DFP), the seryl protease inhibitor, blocks the coagulant activity of the complex and is incorporated into the factor VII (12,18,19); there is no evidence that tissue factor hydrolyzes factor VII during complex formation (19). In native bovine plasma, factor VII incorporates DFP (diisopropylphosphoryl [DIP]-factor VII).…”
Section: Discussionmentioning
confidence: 99%
“…While the complete complex appears to be necessary for coagulant activity (12,17), the factor X converting site appears to reside in the factor VII molecule (18,19). In the bovine system, diisopropylphosphorofluoridate (DFP), the seryl protease inhibitor, blocks the coagulant activity of the complex and is incorporated into the factor VII (12,18,19); there is no evidence that tissue factor hydrolyzes factor VII during complex formation (19). In native bovine plasma, factor VII incorporates DFP (diisopropylphosphoryl [DIP]-factor VII).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced lesions contain smooth muscle cells and macrophages that express tissue factor, and this can be shown to activate the extrinsic pathway of coagulation. 74,75 However, to our knowledge, there have not been careful studies of when this critical initiating factor for the extrinsic pathway is first found during the progress of atherosclerotic lesion formation. Even less is known about the natural expression of tissue factor pathway inhibitor or the presence of annexin V, a cytoplasmic molecule released during cell death that binds phosphatidylserine, a critical cofactor for tissue factor.…”
Section: Intramural Coagulationmentioning
confidence: 99%
“…This finding suggests that factor VII zymogen itself possesses low activity -in the bovine case, approximately 0.8% that of the enzyme [15]. The existence of an unusu ally active catalytic site in factor VII zy mogen is also indicated by the following facts: (a) Factor VII is the only coagulation protein that is inactivated in plasma by diisopropylfluorophosphate (DFP), an irrevers ible inhibitor of serine enzymes [16], (b) The purified single-chain protein incorporates 3H-DFP stoichiometrically [17], (c) DFP in teracts with the zymogen only about 4 times more slowly than with the enzyme [15]; in contrast, trypsinogen reacts with DFP nearly 7,500 times more slowly than trypsin [18], (d) The Km of a synthetic substrate, benzyloxycarbonyl-arginine-p-nitrobenzyl ester is approximately 17-fold higher for factor VII than for factor VIIa, whereas the kcat is only 2-fold lower [19]. Taken together, the evi dence shows that factor VII is much more active than most known zymogens.…”
mentioning
confidence: 99%